PERAN KEPUASAN KONSUMEN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP MINAT BELI KONSUMEN UNTUK MENGGUNAKAN JASA MASKAPAI PENERBANGAN AIR ASIA - Yohanes Febrianto; Tumpal J. R. Sitinjak (Universitas Bunda Mulia, 2017)
In this fast-paced era, high mobility has become necessity for people. They need a fast, simple and cheap transportation.Low cost airlines be an option for people to support their needs. One of the airlines service provider that have low cost concept is Air Asia.This research aims to study the effect of service quality on Air Asia customer purchase intention mediated by customer satisfaction.This research use non-probability sampling with judgement approachment method to collect the data, that the respondent ever used the Air Asia service provider at least once a time. This research collect the data from 150 respondent. The data is collected by the questionnaire and tested by SEM (structural equation modeling) with Lisrel 8.80. The result of this research is there are significant effect between service loyalty and customer satisfaction on customer purchase intention partially and there is a significant effect between service quality on customer purchase intention mediated by customer satisfaction.Keywords: Service Quality, Customer Satisfaction, Customer Purchase Intention